S-Allyl Thiocarbamates from Allylic Alcohols by in situ [3,3]-Sigmatropic Rearrangement of a Thiocarbonyldiimidazole Adduct - Mingat, Gaëlle; Clayden, Jonathan (Synthesis, 2012)
Treatment of allylic alcohols with thiocarbonyldiimidazole generates an unstable O-allyl imidazolyl thione ester, which rearranges spontaneously and in high yield to the corresponding S-allyl imidazolyl thiol ester. Displacement of the imidazole by N-alkylanilines in the presence of a nucleophilic catalyst (HOBt or ECHIA) gives S-allyl N-aryl thiocarbamates in excellent yields (up to 97%) over two steps.
Keywords: sigmatropic rearrangement; thiocarbamates; alcohols; stereospecificity; sulfur